'Just one more episode': Frequency and theoretical correlates of television binge watching. (January 2018) - Walton-Pattison, Emily; Dombrowski, Stephan U; Presseau, Justin
Binge watching is a relatively new behavioural phenomenon that may have health implications. The aim of this study was to estimate the frequency of, and identify modifiable factors associated with, TV binge watching. A total of 86 people completed an online questionnaire assessing self-efficacy, proximal goals, outcome expectations, anticipated regret, automaticity, goal conflict and goal facilitation, and self-reported binge watching over the last week. Participants reported binge watching a mean 1.42 days/week (standard deviation = 1.42). Intention and outcome expectations accounted for variance in binge watching, and automaticity, anticipated regret and goal conflict each separately accounted for additional variance in binge watching. Binge watching is commonplace and associated with both reflective and impulsive factors.